Pelatihan Literasi Keuangan: Cermat Meminjam dan Menabung - Misfi Laili Rohmi; Nur Syamsiyah; Lilis Renfiana; Carmidah Carmidah Carmidah (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2024)
This service activity aims to provide an understanding of financial literacy (careful borrowing and saving) so that it is hoped that participants can avoid loan sharks. Apart from that, participants are given knowledge about making simple financial reports so that expenses do not exceed income. This service was carried out at the Women's Farmers Group (KWT) in Pagelaran Village, Pringsewu Regency. The service method used is material presentation and discussion. The results of this activity were that the participants generally understood how to choose the right borrowing and saving as well as calculating the size of the costs of borrowing, although there were some participants who had a little difficulty in reading and writing.